Limit theorems for Floyd's triangle: a new approach to not a new problem - Belovas, Igoris (Lietuvos matematikos rinkinys, 2021)
Floyd's triangle is often presented to computer science students as an exercise or example to illustrate the concepts of text formatting and loop constructs. The paper proposes to look at an object from a different angle and to examine limit theorems for the numbers of generalized Floyd's triangles. Tasks of this type can be used as exercises in study programs of mathematics and informatics (couses of probability theory and combinatorics). It would help to master the appropriate proof techniques and mathematical apparatus. The article proposes a series of possible problems and their proof schemes.
Keywords: Floyd's triangle; limit theorems; uniform distribution